First Episodes of Norovirus and Sapovirus Gastroenteritis Protect Against Subsequent Episodes in a Nicaraguan Birth Cohort. Issue 5 (10th June 2022) - Vielot, Nadja A.; Reyes, Yaoska; Blette, Bryan; González, Fredman; Toval-Ruiz, Christian; Gutiérrez, Lester; Vilchez, Samuel; Diez-Valcarce, Marta; Vinjé, Jan; Becker-Dreps, Sylvia; Bucardo, Filemón
Abstract : Background: Norovirus and sapovirus cause a large burden of acute gastroenteritis (AGE) in young children. We assessed protection conferred by norovirus and sapovirus AGE episodes against future episodes. Methods: Between June 2017 and July 2018, we recruited 444 newborns in León, Nicaragua. Weekly household surveys identified AGE episodes over 36 months, and AGE stools were tested by reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) for norovirus genogroup (G)I/GII and sapovirus. We used recurrent-event Cox models and negative control methods to estimate protection conferred by first episodes, controlling for observed and unobserved risk factors, respectively. Results: Sapovirus episodes conferred a 69% reduced hazard of subsequent episodes using the negative control method. Norovirus GI (hazard ratio [HR] = 0.67; 95% confidence interval [CI] = 0.31, 1.3) and GII (HR = 0.20; 95% CI = 0.04, 0.44) episodes also appeared highly protective. Protection against norovirus GII was enhanced following two episodes. Conclusions: Evidence of natural immunity in early childhood provides optimism for the future success of pediatric norovirus and sapovirus vaccines.